Predictors of Residence Hall Involvement (2003)
Residence hall students' (N = 1,186, 52% male, 90% White, 66% freshmen) involvement in their living community is influenced significantly by precollege student characteristics (gender, ethnicity), classification, attitudes (toward hall director, house cabinet, academic comfort, social environment, group study), and environmental variables (noise, time spent in the house, residence assistant interaction, peer academic conversations, employment).